International Management / Managing Across Borders and Cultures - Deresky Helen (Prentice Hall, 2011)
Preface, The Global Manager's Environment, Assessing the Environment: Political and Economic and Legal and Technological, Managing Interdependence: Social Responsibility and Ethics, The Cultural Context of Global Management, Understanding the Role of Culture, Communicating Across Cultures, Cross-Cultural Negotiation and Decision Making, Formulating and Implementing Strategy for International and Global Operations, Formulating Strategy, Global Alliances and Strategy Implementation, Organization Structure and Control Systems, Global Human Resources Management, Staffing and Training and Compensation for Global Operations, Developing a Global Management Cadre, Motivating and Leading, Integrative Section, Intgrative Team Project, Glossary, Endnotes, Name and Subject Index.
Preface, The Global Manager's Environment, Assessing the Environment: Political and Economic and Legal and Technological, Managing Interdependence: Social Responsibility and Ethics, The Cultural Context of Global Management, Understanding the Role of Culture, Communicating Across Cultures, Cross-Cultural Negotiation and Decision Making, Formulating and Implementing Strategy for International and Global Operations, Formulating Strategy, Global Alliances and Strategy Implementation, Organization Structure and Control Systems, Global Human Resources Management, Staffing and Training and Compensation for Global Operations, Developing a Global Management Cadre, Motivating and Leading, Integrative Section, Intgrative Team Project, Glossary, Endnotes, Name and Subject Index.